INTERNALISASI NILAI-NILAI KARAKTER MELALUI PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR ISLAM TERPADU AL MUMTAZ PONTIANAK - Zaenuri yarso; Marzuki Marzuki; Yulis Jami ah (Universitas Tanjungpura, 2019)
Abstract The main educational issues today are quality and character. Integrated thematic learning in Elementary School is expected to be a solution. This study aimed to describe the implementation of integrated thematic learning as well as the internalization of the nation's character values, including religious and disciplinary characters. This is descriptive qualitative research, described fact and phenomenon in detail and intact. Researcher served as an instrument of data collection. This subject is the fourth-grade teacher of A SDIT Al Mumtaz. Techniques of collecting data used: interviews, observation, and documentation. Data validity was obtained by triangulation. Data analysis includes data reduction, analysis, and conclusions. The conclusion of the study: first, integrated thematic learning at SDIT Al Mumtaz combined of the 2013 curriculum with SIT concept from JSIT Indonesia. The combination of enrichment in the material and the learning process (steps T-E-R-P-A-D-U). Second, internalization of values through exemplary, habituation, advice and lessons, attention and supervision, and reward and punishment. Third, supporting factors such as the concept of JSIT, young teachers and fast learners, and commitment to synergy parents of learners. Keywords: character, internalized values, thematic integrated